2018
DOI: 10.1111/jocd.12812
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficacy of microneedle fractional radiofrequency in Turkish patients with atrophic facial acne scars

Abstract: Summary Background Scarring is an undesirable and severe complication of acne resulting in loss of self‐esteem in young people. Although microneedle fractional radiofrequency (MFR) system has emerged as a good option to treat acne scars in recent years, it was examined in a few studies which were commonly from Asian countries. Aims We sought to evaluate the efficacy of MFR in Turkish patients with facial acne scars. Methods Nine patients with atrophic facial acne scars treated with MFR device were included in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
4
7
0
1
Order By: Relevance
“…A high rate of patient satisfaction was reported in almost all patients undergoing FmRF treatment . In a recent study in nine patients with atrophic acne scars, use of FmRF was reported to be associated with a favorable efficacy and safety with clinical improvement of >25% in seven patients (77.7%) and no severe side effects . In another study among 19 patients with acne scars, a series of 2‐6 sessions of noninsulated FmRF treatment was reported to offer a highly effective minimally invasive treatment for acne scars and improvement of skin texture and pore size with a short downtime and high patient satisfaction rates…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A high rate of patient satisfaction was reported in almost all patients undergoing FmRF treatment . In a recent study in nine patients with atrophic acne scars, use of FmRF was reported to be associated with a favorable efficacy and safety with clinical improvement of >25% in seven patients (77.7%) and no severe side effects . In another study among 19 patients with acne scars, a series of 2‐6 sessions of noninsulated FmRF treatment was reported to offer a highly effective minimally invasive treatment for acne scars and improvement of skin texture and pore size with a short downtime and high patient satisfaction rates…”
Section: Discussionsupporting
confidence: 91%
“…8,14 In a recent study in nine patients with atrophic acne scars, use of FmRF was reported to be associated with a favorable efficacy and safety with clinical improvement of >25% in seven patients (77.7%) and no severe side effects. 15 In another study among 19 patients with acne scars, a series of 2-6 sessions of noninsulated FmRF treatment was reported to offer a highly effective minimally invasive treatment for acne scars and improvement of skin texture and pore size with a short downtime and high patient satisfaction rates. 16 Accordingly, our findings revealed 44% decrease in average ECCA scores from baseline with the FCL + FmRF combination treatment and majority (90.3%) of patients reported that they were satisfied with treatment.…”
Section: Correlation Of Ecca Scores With Study Variablesmentioning
confidence: 99%
“…It was established in a retrospective study including nine patients that at least 25% clinical improvement was achieved in about 80‐90% of patients after an average of three FRF treatments 8 9 .…”
Section: Discussionmentioning
confidence: 99%
“…of patients after an average of three FRF treatments. 8 Another study revealed improvement in scars and erythema starting from the second treatment session with double-pass FRF once a month. 9 A meta-analysis of six studies, each of them including 20-33 cases and controls, comparing FRF with fractional laser (FCO 2 in four and 1550 nm Er:Glass fractional laser in two studies) in the treatment of atrophic acne scars in Asian population demonstrated that both laser and FRF produced similar results in terms of clinical efficacy.…”
Section: Patient Efficacy Evaluations Of Fco 2 and Frf Plus Fcomentioning
confidence: 99%
“…29 According to another study conducted on 9 Turkish patients with facial acne atrofic scars, which were treated with fractional microneedle RF, a clinical improvement of more than 25% has been reported in almost all the patients, boxcar scars achieving the best results. 30 Ramesh et al used fractional bipolar RF in a study aimed to analyze which specific type of atrophic acne scar responds better to this treatment. They found that ice-pick scars had best results to treatment, followed by rolling and boxcar.…”
Section: Fractional Radiofrequency Treatment In Atrophic Acne Scarsmentioning
confidence: 99%